Role and motivation of mental health nurses in the implementation of ‘restraint free’ program in Mataram primary health care of West Nusa Tenggara - Arif Rahman; Carla Raymondalexas Marchira; Ibrahim Rahmat (Berita Kedokteran Masyarakat (BKM), 2016)
Role and motivation of mental health nurse in “restraint free” program: a case study from MataramPurposeThis study aimed to describe the mental health nurse’s role and motivation of the implementation of a ‘restraint free’ program (program bebas pasung) at community health centers, Mataram, West Nusa Tenggara.MethodsThis was a qualitative research with case study design. The subjects were ten nurses of mental health programs, three persons from families of sufferers, two employees of community health service and one person who was a former sufferer of a mental disorder. Data collection used focus group discussions (FDG), in-depth interviews and observations. ResultsThe nurses had been carrying out their role as executors of nursing care policy, as the direct nursing caregivers, and were giving the nursing to sufferers and their families as well as continuing therapy for sufferers, and as educators also educated the family. Mental health information provided guidance to intern students doing mapping of cases of mental disorders and empowering the sufferer. The form of the work involves motivation of nurses while working conditions were a factor that cannot support nurses for giving the nursing care to suffers and family. ConclusionNurses have been implementing a ‘restraint free’ program. however, it has not been always well received in the working conditions experienced. So, it is recommended that mental health nurses be given help and support partners or stakeholders to enhance preventive efforts, in their promotive, curative and rehabilitative programmes.